The Effectiveness of Customs Policy on the Internationalization Process of Furniture MSMEs in Pasuruan: A Case Study Based on Regulatory Compliance - Wisma Miftahur Rozi; Sudarmiatin; Heri Pratikto (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to analyze the effectiveness of customs policy on the internationalization process of furniture MSMEs in Pasuruan by emphasizing the regulatory compliance aspect. This study uses a qualitative approach with a case study method on one of the furniture MSMEs that has carried out export activities. Data collection was carried out through in-depth interviews, observations, and documentation related to export procedures and compliance with customs requirements. The results of the study show that customs policy has a significant role in determining the smooth export process, especially in the aspects of administration, classification of goods, and fulfillment of export documents. The level of understanding of MSME actors with applicable regulations is a key factor in increasing compliance and minimizing export barriers. However, procedural complexity, limited regulatory literacy, and dynamic policy changes are still the main obstacles in the internationalization process. On the other hand, government support through socialization, digitization of customs services, and export facilitation has proven to be able to increase the readiness of MSMEs to penetrate the global market. This study concludes that the effectiveness of customs policies is not only determined by the regulations themselves, but also by the level of adaptation and compliance of MSMEs to the applicable regulations. The implications of this study emphasize the importance of increasing legal literacy and strengthening the assistance system for MSMEs to increase export competitiveness in a sustainable manner.